DIGITAL MARKETING DALAM RANGKA MENGEMBANGKAN USAHA ERNA SARI CATERING - Ely Suhayati; Windi Novianti; Cun Figitria Panca Rhema; Defitri Agustini (Universitas Komputer Indonesia, 2022)
Digital marketing is seen as the best media as the most effective and efficient means of promotion and is able to increase sales volume significantly in business development. The purpose of this study is to describe digital marketing strategies in order to develop Erna Sari Catering business. The research method used is descriptive qualitative through data collection obtained from Erna Sari Catering through interviews, surveys, literature studies, and observation. The results of this study assist government programs in reducing the unemployment rate due to the Covid-19 pandemic, such as providing job vacancies in digital marketing as a marketing tool for products and services. To increase product marketing and get business opportunities, one of the ways or strategies used by Erna Sari Catering is by utilizing information technology developments that provide opportunities for Erna Sari Catering's business to reach a wider market through the implementation of digital marketing through the website. Therefore, with a broad digital marketing reach, it allows Erna Sari Catering's business to reach more customers, thus making Erna Sari Catering's business grow. Key Words : Digital Marketing, Company Development, Erna Sari Catering